D-modules on rigid analytic spaces II: Kashiwara's equivalence - Ardakov, K; Wadsley, S (American Mathematical Society, 2018)
Let X be a smooth rigid analytic space. We prove that the category of co-admissible D͡X-modules supported on a closed smooth subvariety Y of X is naturally equivalent to the category of co-admissible D͡Y- modules, and use this result to construct a large family of pairwise non-isomorphic simple co-admissible D͡X-modules.